STRUKTUR GERAK TARI SELODANG MAYANG DI KERATON KESULTANAN KADRIYAH PONTIANAK KALIMANTAN BARAT - Utami, Riana; Fretisari, Imma; Tindarika, Regaria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research is motivated by the desire of researchers to describe the structure of the Selodang Mayang dance movement. This research uses a descriptive method in a qualitative form and uses an ethnochoreological approach, with data sources in the form of Selodang Mayang Dance. The speakers in this study were Syarifah Zainab Asgaf, Syarifah Fadlon Alkadrie and Syarifah Faizah Alkadrie who knew about Selodang Mayang dance at the Kadriyah Sultanate Palace in Pontianak, West Kalimantan. Data collection techniques such as observation, interviews and audio-visual material. The data validity testing technique used is the extension of observation and source triangulation. Based on the analysis of the data it was concluded that the structure of the Selodang Mayang dance movement in the Kadriyah Sultanate Palace in Pontianak, West Kalimantan as follows: The name Selodang Mayang dance was taken from the property names namely shawl and mayang. Selodang Mayang dance is a group dance. There are 3 types of motion that are described based on the smallest part first, namely the motive motions, motion phrases, sentences of motion and groups of motion that become a unified whole of motion in the Selodang Mayang dance. The motion in Selodang Mayang dance is identical with double step or double foot or usually called jogog dance.Keywords: Dance, Motion structure, Selodang Mayang